By Force of Confidence - Vincenzo Merella; Stephen Satchell (Prague University of Economics and Business, Faculty of International Relations (FIR), 2020)
Recent macro-finance contributions explain a great deal of unconditional asset pricing by introducing persistent consumption risks and rare disasters. Only the volatility puzzles remain unresolved among the longer-established issues in this literature. Motivated by empirical finance contributions and conventional wisdom, we abstract from a consumption-centric analysis and let the asset-pricing kernel depend on habit formation and consumer confidence as a demand shifter correlated with consumption growth. The resulting model compares favorably with the literature in explaining the risk-free rate volatility, but it falls short in matching the standard deviation of the market return. Our findings justify using supplementary information to price assets while warning against neglecting a thorough analysis of consumption growth dynamics.
Keywords: G12; E21; 330; Asset Pricing; Consumer Confidence; Habit Persistence; Recursive Utility; Utility from Anticipation; Year-on-Year Growth